A WAVE RESONANCE STUDY IN HARBORS WITH A HYPERBOLIC-COSINE SQUARED BOTTOM - Farrell Pradharma, Juan
The wave resonance phenomenon in a harbor can cause damage around the area. One of the causes of this resonance phenomenon is the natural harbor resonance period. A resonance phenomenon will occur when an external force enters the harbor mouth with a period similar to the natural harbor period. In this study, we will observe the natural period of harbors with a hyperbolic-cosine squared bottom. We obtain this natural period analytically using the shallow water equations. Then, using the staggered finite volume method, we will perform some numerical simulations to confirm and detect the existence of resonance. Further, we will add roughness to the harbor bottom and determine the effective friction coefficient required to prevent resonance phenomena. Finally, we will apply the model to Palu Bay in Central Sulawesi.